Review of Preterm Labour Cases at Dr. Cipto Mangunkusumo Hospital January – December 2009 - Andi Fatimah (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To describe and to evaluate preterm labour cases and management at obstetric emergency room of Dr. Cipto Mangunkusumo Hospital (RSCM) from January until December 2009. Method: This is a cross-sectional study with 202 secondary data samples from stratified random sampling performed to all preterm labour cases at obstetric emergency room of RSCM from January until December 2009. The data were processed for frequencies and bivariate analysis, and then further analyzed with multivariate analysis. Result: Most of the patient’s age were between 17 to 35 years old (82.7%). Most of them belonged to preterm group or gestational age between 32 weeks to less than 37 weeks (69.8%). Fifty three percent of the preterm labour was caused by premature rupture of the membrane. About 47% of the babies had perinatal morbidity and the most morbidity cases was respiratory distress with septic condition (47.7%). Perinatal mortality only happened to 5.9% babies. From bivariate analysis, low socioeconomic level (p = 0.032), gestational age (extreme preterm p = 0.000, very preterm p = 0.000), APGAR Score minute 1 < 7 (p = 0.000), APGAR Score minute 5 < 7 (p = 0.000) and preterm baby status (Small for Gestational Age p = 0.048) were the variable which influenced the perinatal morbidity in our hospital. Perinatal mortality was influenced by low socioeconomic level (p = 0.048), gestational age (extreme preterm p = 0.000, very preterm p = 0.063), APGAR Score minute 1 < 7 (p = 0.000), APGAR Score minute 5 < 7 (p = 0.000) and also morbidity of the preterm baby (p = 0.000). In this study, we found there was significant relation between cases of membrane rupture and perinatal sepsis (p = 0.000; RR 5.98; 95% CI 2.72 - 13.39) but there was no significant relation between cases with or without membrane rupture compared to active or expectant management to the perinatal morbidity and mortality. From multivariate analysis, APGAR score minute 5 < 7 had the greatest influence to the perinatal morbidity and preterm baby morbidity had the greatest influence to perinatal mortality. Conclusion: Perinatal morbidity and mortality caused by preterm labour in Dr. Cipto Mangunkusumo Hospital were influenced by several factors which are socioeconomic status, APGAR score, preterm baby status and also morbidity of the baby. Therefore we need to do comprehensive prevention in biologic and socioeconomic condition of the patients. Expectant management in preterm labour cases should be made on many consideration since expectant management was proven had no correlation with good perinatal morbidity and mortality outcome. [Indones J Obstet Gynecol 2011; 35-2: 61-6] Keywords: preterm labour, risk factor, perinatal morbidity, perinatal mortality